Fabrication of mesoporous carbon supported Ni-Mo catalysts for the enhanced conversion of glucose to ethylene glycol - Kirali, Arun Arunima; Sreekantan, Sreejith; Marimuthu, Banu (New Journal of Chemistry, 2020)
Mesoporous carbon (MC)-supported Ni-Mo catalysts with varying amounts of Ni (x= 0, 3, 6 and 9 wt%) and Mo (y= 0, 10, 15 and 20 wt%) were prepared using the wet-impregnation method and characterized. Their catalytic activity in the selective conversion of aqueous glucose solution (15 wt%) to ethylene glycol (EG) in a batch reaction was investigated. A catalyst, with 3% Ni and 15% Mo on MC showed the highest activity and selectivity. The complete conversion of glucose with 63.2% yield of EG was obtained in a reaction conducted for 6 h at 200 degrees C and 40 bar hydrogen pressure. A synergistic enhancement in catalytic performance was found when both Ni and Mo were present in the catalyst composition. The dispersion of Mo enhanced in presence of Ni and a part of Mo was reduced from +6 to lower oxidation states (+5 and +4), which imparted the acidity of the catalyst. Ni facilitated the hydrogenation activity and acid sites on Mo led to the retro-aldol reaction forming higher amounts of EG. The catalyst was found to be reusable.